Strategies to Increase Student Interest in the Superior Al-Qur'an Memorization Program in Elementary Schools - Sari, Anita; Sari, Meilida Eka; Heru Prasetyo; Jefryadi, Jefryadi (Program Studi Pendidikan Islam Anak Usia Dini, Institut Agama Islam Ma'arif (IAIMNU) Metro Lampung, 2025)
This study aims to analyze the strategies used to enhance students’ interest in the Tahfidz Al-Qur’an program at SD Aisyiyah Lubuk Linggau, one of the school’s flagship programs designed to strengthen religious competence and character formation at the elementary level. Using a qualitative descriptive approach, data were collected through observation, interviews, and documentation to explore pedagogical practices, managerial arrangements, and supporting factors within the learning environment. The findings indicate that students’ interest grows significantly when learning activities are designed to be enjoyable, relevant, and meaningful. Teachers employ various pedagogical strategies, including games, kinesthetic activities, rhythmic repetition, talaqqi, and inspirational storytelling, which successfully increase students’ engagement and intrinsic motivation. Managerial strategies—such as flexible scheduling, ability-based grouping, and continuous evaluation—contribute to reducing learning pressure and increasing students’ confidence. Social support from parents, reinforced through daily hafalan control books and school appreciation events like Tahfidz graduation ceremonies, further strengthens students’ consistency and sense of belonging to the Tahfidz community. The study concludes that the effectiveness of the Tahfidz program relies not only on structured curriculum design but also on integrated strategies that respond to students’ psychological needs and developmental characteristics. These findings offer theoretical and practical implications for improving Tahfidz programs in elementary schools and highlight the need for further research using broader and comparative approaches.